KOMPETENSI PEGAWAI, SISTEM INFORMASI, BUDAYA ORGANISASI, KUALITAS PEMERIKSAAN KEBERATAN DI BIDANG KEPABEANAN: PERAN MODERASI KEPEMIMPINAN - Yusuf Dwi Arwianto; Amrie Firmansyah; Iskandar Iskandar (Universitas Multimedia Nusantara, 2023)
Abstract— This study aims to examine the effect of employee competence, information systems, and organizational culture on the quality of customs objection examination with leadership as a moderating variable. The type of research used in this study is correlational with a quantitative approach. Data were collected using a questionnaire method and analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis. The results showed that employee competence and organizational culture had no effect on the quality of objection examinations in the customs sector, while the information system had a positive effect on the quality of objection examinations in the customs sector. Furthermore, the interaction of leadership and employee competence actually has a negative effect on the quality of objection examinations, but it does not strengthen the positive influence of information systems and organizational culture on the quality of objection examinations in the customs sector. Keywords: Competence; Information Systems; Organizational Culture; Leadership; Examination Quality